Plan de negocios aplicando el modelo Mycoop para la asociación Asopicir del municipio de Circasia del departamento del Quindío beneficiaria de la Fundación Fundecompe. (2016)
to give fulfillment to the main objective of the project, which is the development of a business plan under the Mycoop methodology for the Asopicir Association, in the first instance there was a diagnosis quantitative and comprehensive of all areas of the Association, in order to meet its initial state and analyze strengths, weaknesses, opportunities and threats consecutively it was formulated to a business plan focused on the most critical areas and with greater need to be strengthened, focusing it on marketing, the modernization of machinery and the adequacy of facilities, using its structuring Mycoop methodology created by the ILO, especially for strengthening organizations farming as is the case of Asopicir. As a complement to the business plan trainings were conducted on general topics of interest to the members of the Association, as a management TIC´S and management of resources; Finally the socialization of business planheld and prepared for the Association, focusing on this towards the awareness and empowerment of partners for the execution of the project and the achievement of resources through the calls made by the Ministry of agriculture. Complying well with the last raised goal.